The Lesbian and gay studies reader - Abelove, Henry; Barale, Michèle Aina; Halperin, David M. (Routledge, 1993)
Rassemblant quarante-deux essais révolutionnaires, dont beaucoup sont déjà des classiques, The Lesbian and Gay Studies Reader fournit une introduction indispensable à l'état contemporain des études lesbiennes/gay, illustrant largement l'étendue, la portée, la diversité, l'attrait et puissance du travail actuellement réalisé dans le domaine. Présentant des essais d'éminents chercheurs tels que Judith Butler, John D'Emilio, Kobena Mercer, Adrienne Rich, Gayle Rubin et Eve Kosofsky Sedgwick, The Lesbian and Gay Studies Reader explore une multitude d'expériences sexuelles, ethniques, raciales et socio-économiques. . S'étendant sur des disciplines telles que l'histoire, la littérature, la théorie critique, les études culturelles, les études afro-américaines, les études ethniques, la sociologie, l'anthropologie, la psychologie, les classiques et la philosophie, cette anthologie retrace l'inscription des significations sexuelles dans toutes les formes d'expression culturelle. Représentant le meilleur et le plus important travail en langue anglaise dans le domaine, The Lesbian and Gay Studies Reader aborde des sujets tels que les rôles butch-fem, la construction culturelle du genre, le séparatisme lesbien, la théorie féministe, le sida, l'éducation sexuelle sans risque, le colonialisme, le S /M, Oscar Wilde, Gertrude Stein, les livres pour enfants, le nationalisme noir, les films populaires, Susan Sontag, le placard, l'homophobie, Freud, Sappho, les médias, les hijrasde l'Inde, Robert Mapplethorpe, et la politique de représentation. Il contient également un essai bibliographique détaillé qui fournira aux lecteurs un guide inestimable pour des lectures complémentaires. Contributeurs :Henry Abelove, Tomas Almaguer, Ana Maria Alonso, Michele Barale, Judith Butler, Sue-Ellen Case, Danae Clark, Douglas sertissage, Teresa de Lauretis, John D'Emilio, Jonathan Dollimore, Lee Edelman, Marilyn Frye, Charlotte Furth, Marjorie Garber , Stuart Hall, David Halperin, Phillip Brian Harper, Gloria T. Hull, Maria Teresa Koreck, Audre Lorde, Biddy Martin, Deborah E. McDowell, Kobena Mercer, Richard Meyer, DA Miller, Serena Nanda, Esther Newton, Cindy Patton, Adrienne Rich, Gayle Rubin, Joan W. Scott, Daniel L. Selden, Eve Kosofsky Sedgwick, Barbara Smith, Catharine R. Stimpson, Sasha Torres, Martha Vicinus, Simon Watney, Harriet Whitehead, John J. Winkler, Monique Wittig et Yvonne Yarbro -Bejarano
http://bvbr.bib-bvb.de:8991/exlibris/aleph/a23_1/apache_media/DLCIQ4G6YQGKSDIDV2CF3NB8T7FQBI.pdf
Keywords: approches et analyses; corps; cours; discours dominant; histoire et politique; hétérosexisme; lesbianisme; outils; ouvrages de références; racisme; santé; sexualité; soc2014; système colonial; systèmes d'oppressions; thématiques; violences

Les femmes autochtones et la justice pénale - Jaccoud, Mylène (Criminologie, 1992)
The interest in understanding and analyzing the situation of native women within the penal process is recent and seems to be limited by the inordinate attention paid by researchers to the overrepresentation of native women. This article is an account of the findings and analyses made to date in this recent sector of research. It presents an inventory of the principal data concerning the confrontation of native women with the penal process. It proposes a synthesis of the principal analyses of the problems of native women with the system of justice by presenting a critical analysis of the socio-structural model of LaPrairie.
Keywords: amériques; approches et analyses; canada; cours; criminologie; discipline; droit; droits des femmes*; droits des femmes* autochtones; histoire et politique; intersectionnalité; justice sociale; pol4105; premier cycle; racisme; régions géographiques; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Exotisme et altérité: Essai sur les fondements d'une critique de l'anthropologie - Affergan, Francis (Presses universitaires de France, 1987)
Section: 295 pages
Keywords: anthropologie; approches et analyses; cours; discipline; har4610; histoire et politique; premier cycle; racisme; sciences humaines; système colonial; systèmes d'oppressions; thématiques; violences

The Traditional Roles of Native Women in Canada and the Impact of Colonization - Brodribb, Somer (The Canadian Journal of Native Studies, 1984)
Recent trends in feminist research indicate a growing interest in the impact of Native women on westward expansion and imperialism. The author suggests that while early European contacts affected the status of women negatively, the views of Native women were seldom recorded during these early contact periods. Recent studies have examined the status and changing roles of Native women from the viewpoints of contemporary Native women. The diversity of their opinions continues to be a part of the contemporary debate on the resilience and resourcefulness of Native women in the past.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 1970-1979; 1980-1989; amériques; approches et analyses; canada; cours; discipline; famille; féminisme autochtone; histoire et politique; intersectionnalité; mariage; pol4105; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; sociologie; sofia; système colonial; systèmes d'oppressions; thématiques; violences

The Destruction of American Indian families - Unger, Steven (Association on American Indian Affairs, 1977)
Responding to the need for a comprehensive source of information regarding the separation of American Indian children from their families, this book presents essays which: examine the Indian child-welfare crisis in contemporary, legal, and historical perspectives; document the human cost of the crisis to Indian parents, children, and communities; and report on innovative programs designed and implemented by the Indian tribes themselves. Specifically, this book includes the following sections and essay titles: (1) Contemporary Overviews ("The Destruction of American Indian Families" and "The Role of the Federal Government: A Congressional View"); (2) Historical Perspectives ("The Effects of Boarding Schools on Indian Family Life: 1928" and "'Kid Catching' on the Navajo Reservation: 1920"); (3) The Human Cost ("'The Drunken Indian': Myths and Realities"; "The Wasted Strengths of Indian Families", "The Human Cost of Removing Indian Children from Their Families", "Child-Welfare Services to Indian People in the Albuquerque Area", "Indian Child Welfare in Oregon", "The Ravage of Indian Families in Crisis", "The Question of Best Interest", and "The Placement of American Indian Children–The Need for Change"); (4) A Legal Perspective ("Parent and Child Relationships in Law and in Navajo Custom"); (5) Tribal Actions ("Indian Children and Tribal Group Homes: New Interpretations of the Whipper Man" and "Tribal Resolutions"). (JC)
Keywords: american indian families; amériques; approches et analyses; autochtones; cours; discipline; droit; famille; his4443; histoire et politique; premier cycle; racisme; racisme systémique; residential schools; régions géographiques; science politique; science politique et droit; sciences humaines; sociologie; système colonial; systèmes d'oppressions; thématiques; violence coloniale; violence systémique; violences; états-unis